Clinical Features of COVID-19 on Patients With Neuromyelitis Optica Spectrum Disorders - Apostolos-Pereira, Samira Luisa; Campos Ferreira, Lis; Boaventura, Mateus; de Carvalho Sousa, Nise Alessandra; Joca Martins, Gabriela; d'Almeida, José Arthur; Pitombeira, Milena; Silvestre Mendes, Lucas; Fukuda, Thiago; Souza Cabeça, Hideraldo Luíz; Chaves Rocha, Luciano; Santos de Oliveira, Bianca; et al. (Wolters Kluwer, 2021)
BACKGROUND AND OBJECTIVES: To describe the clinical features and disease outcomes of coronavirus disease 2019 (COVID-19) in patients with neuromyelitis optica spectrum disorder (NMOSD). METHODS: The Neuroimmunology Brazilian Study Group has set up the report of severe acute respiratory syndrome (SARS-CoV2) cases in patients with NMOSD (pwNMOSD) using a designed web-based case report form. All neuroimmunology outpatient centers and individual neurologists were invited to register their patients across the country. Data collected between March 19 and July 25, 2020, were uploaded at the REDONE.br platform. Inclusion criteria were as follows: (1) NMOSD diagnosis according to the 2015 International Panel Criteria and (2) confirmed SARS-CoV2 infection (reverse transcription-polymerase chain reaction or serology) or clinical suspicion of COVID-19, diagnosed according to Center for Disease Control / Council of State and Territorial Epidemiologists (CDC/CSTE) case definition. Demographic and NMOSD-related clinical data, comorbidities, disease-modifying therapy (DMT), COVID-19 clinical features, and severity were described. RESULTS: Among the 2,061 pwNMOSD followed up by Brazilian neurologists involved on the registry of COVID-19 in pwNMOSD at the REDONE.br platform, 34 patients (29 women) aged 37 years (range 8-77), with disease onset at 31 years (range 4-69) and disease duration of 6 years (range 0.2-20.5), developed COVID-19 (18 confirmed and 16 probable cases). Most patients exhibited mild disease, being treated at home (77%); 4 patients required admission at intensive care units (severe cases); and 1 patient died. Five of 34 (15%) presented neurologic manifestations (relapse or pseudoexacerbation) during or after SARS-CoV2 infection. DISCUSSION: Most NMOSD patients with COVID-19 presented mild disease forms. However, pwNMOSD had much higher odds of hospitalization and intensive care unit admission comparing with the general Brazilian population. The frequency of death was not clearly different. NMOSD disability, DMT type, and comorbidities were not associated with COVID-19 outcome. SARS-CoV2 infection was demonstrated as a risk factor for NMOSD relapses. Collaborative studies using shared NMOSD data are needed to suitably define factors related to COVID-19 severity and neurologic manifestations.